The oral manifestations and related mechanisms of COVID-19 caused by SARS-CoV-2 infection - Lin, Weiming; Gao, Feng; Wang, Xia; Qin, Nianhong; Chen, Xianxiong; Tam, Kin Yip; Zhang, Chengfei; Zhang, Mingxia; Sha, Ou (Frontiers in Cellular Neuroscience, 2023)
Coronavirus disease 2019 (COVID-19) was reported to be associated with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection, and patients present mostly with respiratory symptoms. There have been an increasing number of reports on oral manifestations, and some of these signs are informative in terms of identifying SARS-CoV-2 infection. The goal of present study was to review and synthesize the clinical characteristics and underlying mechanisms of COVID-19 oral manifestations, as well as to evaluate the factors influencing SARS-CoV-2 infectivity, in order to conduct further in-depth investigations and help clinicians diagnose COVID-19 patients exhibiting oral symptoms.